Análise e redimensionamento de uma rede industrial de distribuição de ar comprimido: estudo de caso em uma empresa de fundição - Sganzerla, Henrique Artuzo (2018)
Compressed air is considered one of the major forms of mechanical energy, which has resulted in widespread use in industry, providing the operation of several equipments and the realization of industrial processes in a safe, efficient and low cost way. However, a pneumatic air system, when wrongly sized, can increase the company's energy consumption and consequently operating costs, as well as causing operating failures at times of high compressed air demand. These problems occurred in the industrial plant analyzed in this case study. Therefore, the main objective of the work is the sizing of a pneumatic air system for a foundry company. Seeking to achieve the objective, it was use a methodology of calculation described by Fialho (2011) for dimensioning the minimum internal pipe size. The present study started with a data collection of compressed air demand, and information about existing problems in the installed system. The analysis of the data allowed the realization of a planning for the sizing of the network and solution of the main problems presented in it. The result was a detailed project in which a layout of the piping system and a list of materials would enable the company to properly install the piping and its accessories, guaranteeing the full operation of all the equipment used in the industrial plant through an efficient system of distribution of compressed air.